A study on the fatigue crack growth behaviour of GTM718 nickel based super alloy under cold-TURBISTAN spectrum loads. (August 2022) - Malipatil, Sharanagouda G.; Nagarajappa, N.; Majila, Anuradha N.; Chandru Fernando, D.; Bojja, Ramesh; Jagannathan, N.; Manjuprasad, M.; Manjunatha, C.M.
Graphical abstract: Highlights: Fatigue crack growth (FCG) behavior under cold-TURBISTAN spectrum load is determined experimentally for GTM718 nickel based super alloy. FCG behavior under cold-TURBISTAN spectrum load is predicted using analytical method with crack driving force, ΔK*. FCG behavior is also predicted by FEA method using FRANC3D software. A fairly good correlation is obtained between the predicted and experimental results. Abstract: In this study, the fatigue crack growth (FCG) behavior of GTM718 nickel base super alloy subjected to cold-TURBISTAN spectrum load sequence was determined by three different methods i.e., (i) Experimental, (ii) Analytical prediction using cycle-by-cycle method and, (iii) Prediction by finite element analysis (FEA). In the experimental method, a standard compact tension (CT) specimen was prepared and pre-cracked to produce a sharp fatigue crack at the notch root. Then, the specimen was subjected to spectrum load blocks repeatedly and crack growth was measured as a function of applied number of flights. Two such tests were carried out in a servo-hydraulic universal test machine with triangular waveform and at an average frequency of 2 Hz. In the second analytical method, the individual load cycles in cold-TURBISTAN spectrum block were separated through rain flow cycle counting method. For each of this counted cycle, the crack extension was determined using crack growth law which was based on two-parameter crack driving force, ΔK*. An in-house MATLAB code was written and used to determine the FCG behavior by cycle-by-cycle method. In the third FEA method, a global model of CT specimen of GTM718 was created in HYPERMESH and a local model with a pre-crack was created in FRANC3D. The FCG behavior under spectrum load was determined using FRANC3D in conjunction with MSC NASTRAN. Two different types of 'FCG law - stress ratio effect' combinations were employed i e., Paris'-Walker (P-W) and Bi-linear-Walker (B-W). The required constants for these laws were derived from the available experimental data of the material. It was observed that the predicted FCG behavior by analytical and FEA methods, although conservative, were fairly good when compared to experimental results.